A systematic review of comparative studies of CO2 and erbium:YAG lasers in resurfacing facial rhytides (wrinkles). (19th May 2017) - Chen, Kee-Hsin; Tam, Ka-Wai; Chen, I-fan; Huang, Shihping Kevin; Tzeng, Pei-Chuan; Wang, Hsian-Jenn; Chen, Chiehfeng (Cliff)
ABSTRACT: Background : Laser resurfacing is used to minimize wrinkles, solar scars and sequelae of acne.Objective : Purpose of the systematic review was to compare resurfacing outcomes of CO2 laser and erbium: yttrium aluminium garnet (erb:YAG) laser therapies.Materials and methods : Medline, Cochrane Library, EMBASE and Google Scholar databases were searched until 9 April 2015 using the following terms: laser, carbon dioxide/CO2, facial wrinkles, rhytides and erbium-doped yttrium aluminium garnet/erbium:YAG/Er:YAG. Two-armed controlled split faced studies that compared CO2 laser and erbium:YAG laser in patients with mild-to-moderate facial wrinkles or rhytides were included.Results : The pooled data in this study and findings of other studies support the greater efficacy with the CO2 laser in improving facial wrinkles, but the erb:YAG laser was associated with a better complication profile compared with the CO2 laser. Except one case of hypopigmentation, other complications (i.e., erythema, hyperpigmentation and crusting) and their rates were reported by studies examining both lasers.Conclusion : In general, the CO2 laser appeared to be more efficacious then the erb:YAG laser in treating facial wrinkles. Both lasers treatments were well tolerated.